2019
DOI: 10.21203/rs.2.11043/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Catastrophic Health Expenditure Incidence and Its Equity in China: A Study on the Initial Implementation of the Medical Insurance Integration System

Abstract: Introduction: By 2013, several regions in China have introduced health insurance integration policies. However, few studies have addressed the impact of medical insurance integration in China. This study investigates catastrophic health expenditure and equity in the incidence of catastrophic health expenditure by addressing its potential determinants in both integrated areas and non-integrated areas in China in 2013. Methods: The primary data are drawn from the fifth China National Health Services Survey in 20… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…Our study found that catastrophic health expenditure was more likely to be high among males than females, which is consistent with Moradhvaj et al and Liu et al 28,30 The possible explanation might be the type of illness like chronic disease and duration of hospitalisation. A similar finding was reported in Iran, with a significant relationship between chronic disease and catastrophic health expenditure.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study found that catastrophic health expenditure was more likely to be high among males than females, which is consistent with Moradhvaj et al and Liu et al 28,30 The possible explanation might be the type of illness like chronic disease and duration of hospitalisation. A similar finding was reported in Iran, with a significant relationship between chronic disease and catastrophic health expenditure.…”
Section: Discussionsupporting
confidence: 92%
“…Those having family members of 5 or fewer were more likely to incur catastrophic health expenditures. [25][26][27][28] Li et al in China reported that a large family with at least one young member appeared to be a protective factor. 8 However, our study found a likelihood of CHE with a family size five and above at the 10% level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite such policy changes, prior research has been inconclusive about the impact of CMI on out-of-pocket spending. [4] , [5] , [6] , [7] , [8] , [9] Such mixed impacts may be expected when patients with improved insurance choose to seek care at higher-level providers, with an ambiguous impact of higher utilization on their out-of-pocket share of expenditures.…”
Section: Introductionmentioning
confidence: 99%